EFL Lecturers’ Attitudes Towards Local Accented English at IAIN Curup (A Case Study at IAIN Curup) - Paidi Gusmuliana (Corolla International Conference, 2023)
This research looks at how English instructors at IAIN feel about their students’ local accents when they talk in English. The purpose of this study is to investigate lecturers’ attitudes regarding local accents in three dimensions: emotive, cognitive, and behavioral. The researcher employed a combination of methodologies. A concurrent embedded model is a type of mixed approach. This study includes 16 academics for the questionnaire and 6 lecturers for the interview. Questionnaires and interviews were used as research tools. The findings revealed that all instructors had the following sentiments about local accents: Secondly, from an emotional standpoint, English professors at IAIN Curup did not challenge students’ local accents as long as the pronunciation was clear and followed phonological principles. Additionally, according to the instructor, the local accent is not anything to be ashamed of; it reflects a person’s individuality and culture if the pronunciation is proper and does not alter the information to be delivered. Finally, on the behavioral dimension, researchers may closely examine the activities of lecturers. If students’ pronunciation is incorrect and affects the meaning too much, they will be given direct action and promptly corrected. The findings demonstrated that the English instructor at IAIN Curup has a favorable attitude toward the local accents that students have on emotional, cognitive, and behavioral aspects.